Jump ship to freedom - Collier, James L.; Collier, Christopher 1930-. (New York Delacorte Press, 1981)
In 1787 a fourteen-year-old slave, anxious to buy freedom for himself and his mother, escapes from his dishonest master and tries to find help in cashing the solidier's notes received by his father for fighting in the Revolution.
Php 400.00
Donation:Dr. Brian Ventura 04.15.21
Keywords: United States. -- Constitutional Convention -- (1787) -- Fiction; Slavery -- Fiction; African Americans -- Fiction